FAKTOR-FAKTOR INSTITUSIONAL YANG BERPENGARUH PADA NILAI PERUSAHAAN DAN KINERJA KEUANGAN PERUSAHAAN-PERUSAHAAN STARTUP DI NEGARA-NEGARA ASEAN - Retno Yuni Nur Susilowati; Liza Alvia; Neny Desriani (Jurnal Akuntansi dan Keuangan (JAK), 2023)
This research is motivated by the phenomenon of many start-up companies developing in ASEAN countries. This research aims to examine what factors can guarantee the success of startup companies, as assessed by financial performance and firm value. This research includes the variables of investor protection and capital market development as factors that influence the financial performance and firm value of startup companies in ASEAN countries. The data used is startup companies in ASEAN, namely Singapore, Indonesia, and Malaysia. The research data is in the form of financial reports of these companies for the last 5 years (2017-2021). The dependent variables in this research are financial performance (measured by return on invested capital and return on equity) and firm value as measured by Tobin's Q. The results of hypothesis testing show that statistically H1a is supported, meaning that investor protection in a country has a positive effect on the financial performance of startup companies. , whether measured by ROIC or ROE. Next, statistically H1b is supported, meaning that investor protection at the country level has a positive effect on the value of startup companies, as measured by Tobin's Q. Hypothesis testing also shows that statistically H2a is not supported, meaning that the development of a country's capital market has no effect on the company's financial performance. startups. Finally, the test shows that statistically H2b is not supported because capital market developments affect firm value in the opposite direction.